Analisis Penggunaan Media Sosial Membentuk Perilaku Konsumtif pada Generasi Muda - Nurasiah Nurasiah; Naufiza Rahma Lusiani; Nurpazillah H; Rohadi Rohadi; Diki Jamaluddin Ikhsan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of social media has transformed many aspects of young people's lives, particularly in the way they consume information, adopt lifestyles, and interact in the digital world. This study aims to examine how social media use influences the formation of consumerist behavior among young people and its impact on social, psychological, and economic conditions. The research employs a qualitative approach using a literature review method. This method involves examining various journals, books, scientific articles, and documents related to the research topic. The findings indicate that social media is not only used for communication and information seeking but has also become a platform that shapes perceptions of needs, lifestyles, and social identity. Exposure to promotional content, digital trends, influencers, and the culture of following popular developments encourages young people to engage in consumption driven more by desires than by actual needs. In addition to affecting spending patterns, consumerist behavior also influences psychological well-being, social relationships, and individuals' ability to manage their finances. Therefore, strengthening digital literacy and financial literacy is essential to enable young people to use social media wisely and responsibly.